Melanocytoma of the optic nerve head in a young adult - Eulogio Masó Semanat; Margarita Hernández Cunill; Cesar Irarragorri Dorado (Centro Provincial de Información de Ciencias Médicas, 2016)
The case report of a 34 years patient that attended the retina service of "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital in Santiago de Cuba in April, 2012 is described. He had for 3 months approximately, progressive vision decrease in the left eye.  The results of the ophthalmologic and complementary tests confirmed the diagnosis of melanocytoma of the optic nerve head.